1993
DOI: 10.1021/ma00059a023
|View full text |Cite
|
Sign up to set email alerts
|

Living cationic polymerization of isobutyl vinyl ether by hydrogen chloride/Lewis acid initiating systems in the presence of salts: in-situ direct NMR analysis of the growing species

Abstract: Cationic polymerization of isobutyl vinyl ether (IBVE) was carried out with use of the HC1-IBVE adduct [1: CH3CH(OiBu)Cl]/Lewis acid (MX") initiating systems in CH2CI2 at -15 °C. Living polymers were obtained with 1 in conjunction with weak Lewis acids such as ZnCl2 and SnBr4; in contrast, the 1/MX" initiating systems with strong Lewis acids (SnCl4, TiCl4, and EtAlCl2) gave nonliving polymers. However, on addition of ammonium salts (nBu4N+Y~) and phosphonium salts (nBu4P+Y) carrying nucleophilic anions (Y~= Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 2 publications
7
119
0
Order By: Relevance
“…; Chart 2A]. 1,18,23,25 Another method is the use of additives, weak Lewis bases or ammonium salts. Most of the Lewis acids belong to this category.…”
Section: Alcl 3 ðIn Phcocl Ref 9þmentioning
confidence: 99%
“…; Chart 2A]. 1,18,23,25 Another method is the use of additives, weak Lewis bases or ammonium salts. Most of the Lewis acids belong to this category.…”
Section: Alcl 3 ðIn Phcocl Ref 9þmentioning
confidence: 99%
“…9 In 1990, the hydrogen iodide/zinc iodide initiating system in the same solvent and at the same temperature as the previous system was employed for the synthesis of MVE homopolymers and block copolymers with p-methoxy styrene. 21 Finally, in 1993, the IBVE-HCl/nBu 4 NCl/SnCl 4 in dichloromethane at Ϫ78°C was used to polymerize MVE to give homopolymers 22 as well as block copolymers with styrene. 18 This last system was used as the initiator in our synthesis.…”
Section: Polymer Synthesismentioning
confidence: 99%
“…[19][20][21] The results from these investigations suggested that the stabilization of the propagating carbocation through the nucleophilic interaction was of key importance. Along with the development of initiating systems, Higashimura's group, including Sawamoto and us, achieved the living cationic polymerization of various types of functional monomers to give end-functionalized, block, and star-shaped polymers.…”
Section: Introductionmentioning
confidence: 99%